PERANCANGAN INFRASTRUKTUR DAN IMPLEMENTASI WEB SERVER UNTUK WEBSITE SEKOLAH SEBAGAI MEDIA INFORMASI DAN KOMUNIKASI DI SMP PJHI BALIKPAPAN - Ihsan Ihsan; Dwi Lesmideyarti; Qory Hidayati; Tri Retno Nugroho (Jurnal Teknologi Terpadu, 2023)
This research activity in collaboration with partners is carried out with the background of wanting to implement relevant science to solve problems that occur in the community. The world of education, from elementary school to university levels, is required to be able to adapt to rapidly developing technological advances, especially in the field of information. Various ways are carried out by an agency to address the global issue of the 4.0 revolution, where information systems are needed, especially junior high schools that do not yet have a web server as a cloud-based database storage medium and school website facilities as a medium of information to the public. Various information can be provided through the school's website, including school profiles, learning activities, teacher and student achievements and New Student Admissions (PPDB). In this research activity, the implementing team designed a web server and school website using the UML (Unified Modeling Language) and PHP (PHP Hypertext Preprocessor) programming language. The problems faced by partners are the location of the school which is less strategic and the number of applicants is getting smaller every year in the Batakan area of East Balikpapan, does not have informative media for various aspects of interest, the existence of an online PPDB policy from the Education Office to suppress the increase in cases of covid19, limited human resources in the internet and information systems, as well as school quality assurance, namely accreditation. To overcome these problems, SMP PJHI Balikpapan must have its own web server and website. The benefits of online PPDB activities can be carried out so that parents do not need to go to school during registration, and can facilitate the achievement of school accreditation, so as to increase the credibility of the school. The research activities carried out by the team consisted of establishing communication with partners, designing and implementing school servers and websites, providing training on the use of websites, implementing websites in schools.